The Art of Word of Branko Miljković - Aleksić, Slađana V. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The youngest poet of Serbian neosymbolism, Branko Miljkovic, established his version of national poetic tradition according to the well known model of Eliot’s principle and was also always ready to accept something new, modern, the most avant-garde. He argued for the perfection of form as one of important elements of the symbolist poetry within his own poetics as well as within texts related to poetry, while as a poet and translator he was oriented toward modern European poetry of the poet of symbolism with a special talent for patriotic poetry. Branko Miljkovic presents the poem itself as the subject of his poetry where the power of poetic word can be perceived. That structure considers the improvement of lines, the improvement of the expressive power of words as well as the improvement of language. The words are a powerful framework of world for Miljkovic. He strived for returning their depth and intensive meaning. Furthermore, he found creative energy of words, its resurrection in the revival of semantic, evocative and expressive effect. He looked for the value of poetic words primarily within their superiority. In Miljkovic’s world of poetry the words invent, shape, they become the only confirmation of our world. He regarded his poetic opinion and the very act of poet’s creation as a necessary condition of the real poetic creativity: the author identified himself with the very act of writing being completely left at the mercy of words. The art of dying for this world is the art of spiritual living. At the same time it is the effort that differentiates the place of death and the place of life: the poison and the cure. These tendencies provided the poet with intellectual dimension, confirmed not only the power of poetry but the power of poet as well.